(untitled) (Tempo e Argumento, 2022)
Boitatá is a myth of Tupi origin, which protects the fields against those who set them on fire. In the 1960s and 1970s, when the Santa Catarina Island is undergoing a strong modernization process, with an impact on its environment, the folk artist, Franklin Cascaes (1908-1983) invents approximately 30 iconographies for the boitatá, in graphite or pen and ink, invoking him to restore the island mythology. From the approach of the relationship between "myth" and "nature", the article aims to show how Cascaes thought through image, inserting itself in the ecological debate that erupted at the time, in the global sphere. This concern has become increasingly stronger until today, the Anthropocene period, when the human being becomes a geological agent that affects the planet as a whole. In conclusion, a warning is raised, based on theoretical references, to the risk of creating a humanity that excludes all possible others and all other beings that inhabit the Earth. Keywords: Franklin Cascaes ; Boitatá; folklore; myth; ecology.